Treatment of cyanide wastes through bioremediation - Deloya-Martínez, Alma (2016)
This document presents results of research in which an autochthonous consortium of cyanide-degrading microorganisms was developed for use in the biological treatment of hazardous cyanide waste. These autochthonous microorganisms were lyophilized (freeze dried) in different protective media, such as gelatin and lactose broth, at different temperatures (-35,-45,-55 and -65 oC). The preliminary treatment of cyanide wastes involved pretreatment of sludge for 3-5 days to leach the waste, and a subsequent treatment in aerated lagoons, where the consortium of lyophilized microorganisms was applied. Eight different lyophilized samples were obtained at different temperatures using two protective media for lyophilization, which produced excellent results six months after lyophilization. The consortium of lyophilized microorganisms showed 70% to 80% viability, with cyanide extraction percentages higher than 95%, and can be kept active for long periods of time (for years). Lyophilized microorganisms can be used for biodegradation of cyanide wastes from gold mines or from any other cyanide waste such as that from metallic electroplating baths, or from the jewelry manufacturing industry.